Haberde hareketli ve hareketsiz görüntünün kalıcılık ve etkileyicilik açılarından karşılaştırmalı analizi - Kayaalp, Birnur (My University, 2005)
In daily time, visions which we run ınto every part of our lives, supplies to have an idea about individiual or public lifetime realities. It seems that, the image also motivates dominant responses that resinscribe public ideology to inhibit collective memory and public accountability The following report offers a close reading on the mass media as a performance of public judgement. Especially for an instance of television and photography visions.. With this disertation examines the ways in which photographic and televison images can be used in narrative inquiry. It also argue that which visions -photograph or televison- functions as a powerful emotional resource for animating moral delibaration and democratic dissent as it mediates the stronger relation central to public engagement. After introducing the renewed interest in visiual methodology, ıt concludes with some remarks about why photographs can be used more honestly and more directly in research and a resource for public opinion than televisions images. Examplary field which is taken in news and war news area shows photography is much more efective and memorable than video diaries and news programmes in televisions and especially ın news. Among the reason of the differences between televison and photography ımages in news is televisons images's natural substructure, for example fast pictures, musics, special sound and light effects, ancorman's attitude and expression etc. And photograph images's unique and unrepeatable substructure without voice or special effects. Günlük yaşamda her alanda karşılaştığımız görüntüler, toplumların bireylerin, kendilerinden ve yaşamdan haberdar olmalarını sağlamaktadırlar. Aynı zamanda görüntülerin, kamuoyu birliği sağlamada ve kollektif bellek edinmede başat izleyicileri etkilediği görülmüştür. Ekte sunulan raporda kitle iletişim araçları içinde, özellikle de örneklem alanı olarak seçilen televizyon ve fotograf görüntülerinin kamuoyu kararlarını etkilemesini ve hangi aracın halkı en doğru ve tarafsız şekilde olaylardan haberdar ettiği incelenmektedir. Yapılan alan araştırmaları ile güncellenen görüntüsel metod araştırmalarının sonuçları göstermiştir ki televizyon, özellikle haber görüntülerinde tekniğinden ve doğasından kaynaklanan bir takım nedenler ile gerçeği zedeleyici özellikler kazanabilmektedir. Bunun en belirleyici sebepleri arasında fotografın dinamik görsel ve teknik altyapısından kaynaklanan unsurlardır. Hızlı akan resimler, müzik, özel ses ve görüntü efektleri, haberi sunucularının tavır ve ifadeleri gibi teknik ve aracın doğal yapısının içeriği, fotografik görüntülerin ise tekliği ve tekrarlanamaz yapısı ile müzik ve diğer özel efektlere basşvurmaması aradaki belirleyici farkı ortaya koymaktadır. Zira fotograflar sunduğu anlık görüntüler ile anın vurucu yanını yakalamakta, televizyona göre daha sahici ve nesnel görüntüler aktarmaktadır.
Keywords: İletişim_Haber Hazırlama